Cysteinyl-leukotriene receptor antagonist montelukast decreases blood-brain barrier permeability but does not prevent oedema formation in traumatic brain injury - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2009)
Introduction: Traumatic brain injury is highly associated with the over-production of reactive oxygen species. The aim of this study was to investigate the putative neuroprotective effect of montelukast, a cysteinyl-leukotriene receptor antagonist, in a rat model of traumatic brain injury (TBI). Methods: Sprague Dawley rats were subjected to TBI with a weight-drop device using 300 g-1 m weight-height impact. The groups were: control (saline), montelukast (10 mg kg -1 per day, ip), trauma and trauma + montelukast. Two days post-trauma, neurological examination scores were measured and animals were decapitated and the brain tissues were taken for the histologic and biochemical [malondialdehyde (MDA)an index for lipid peroxidation, reduced glutathione (GSH), myeloperoxidase (MPO)an index for neutrophil infiltration and Na +/K +-ATPase activity] evaluations. Brain oedema and blood-brain barrier (BBB) permeability were also evaluated. Results: The neurological examination scores mildly increased in trauma groups at 48 hours. Although the scores were decreased in the montelukast treated group, they were still significantly higher than the control. The trauma caused a significant increase in brain water content and Evans blue (EB) extravasation. Montelukast treatment reduced BBB permeability. It also decreased lipid peroxidation and MPO activity. Conclusion: The present study suggests that montelukast may have beneficial effects against TBI-induced oxidative stress of the brain.
Keywords: Montelukast; cysteinyl-leukotriene; brain injury; closed head; trauma; blood-brain barrier; oedema; antioxidant; neutrophil; INFLAMMATION; ACTIVATION; PROTECTS